Pengelolaan Ketidakefektifan Perfusi Jaringan Perifer Pada Pasien Post ORIF Hari Ke-3 Atas Indikasi Fraktur Femur Dextra 1/3 Distal Di RSUD Ungaran - Anggi Agustina; Mukhamad Musta'in; Maksum Maksum (Universitas Ngudi Waluyo, 2020)
Fracture is the broken continuity of the bone. Based on type and size of the bone, bone can break when it is not strong enough to withstand the pressure applied to the bone. The purpose of this research was to determine the management of the ineffectiveness of peripheral tissue perfusion in Mrs.S suffering from third-day post ORIF with the indication of femur 1/3 distal dextra fracture in Cempaka room, Ungaran Regional Hospital. Management results obtained swollen femur on the third-day post ORIF. It can cause complications due to the ineffectiveness of peripheral tissue perfusion in the patient. A suggestion for nurses in the hospital is to be able to carry out routine observations in post-operative ORIF patients that might experience changing condition. Key words:ROM Exercise, Ineffective Peripheral Tissue Perfusion, Post ORIF